The Impact of Accounting Disclosure on the Volatility of Iraqi Bank Stock Prices Listed on the Iraq Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aimed to determine the impact of accounting disclosure on the price volatility of a sample of Iraqi banks listed on the Iraq Stock Exchange. The main research problem was to determine the potential impact of accounting disclosure in reducing the risks of stock price volatility for banks listed on the Iraq Stock Exchange after a series of economic and geopolitical events experienced by the financial sector in general in Iraq. The research included 7 Iraqi banks that continued to disclose and trade during the period between 2018-2022. The research adopted the quantitative approach in analyzing the data of the study sample banks and reaching its results. The results showed that the level of accounting disclosure in the research sample banks was fairly good, and that they were exposed to different levels of volatility in stock prices, but generally tended towards negative fluctuations. The results also showed a correlation and influence between accounting disclosure and stock price volatility of the Iraqi banks in the research sample.